(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In modern times, the advent of ICT (Information and Communication Technology) offers immense possibilities for the English language learners beyond the confinements of the classroom. Various studies have shown that better understanding of the utilisation of technology for pedagogical purposes is needed for the teachers as well as learners to enhance the quality of learning. Social networking services and various web resources have made learning online a great fun for learners of a foreign language like English. The present day students belong to the digital era and hence most of them are familiar with the use of portable digital devices such as laptops, smartphones, tablets etc. Many studies have shown that the proportion of the population that engages in integrating technology into their routine tasks is increasing over time. However, this novel and dynamic digitized environment, combined with traditional approaches to learning, is yet to be properly harnessed to assist the new generations of learners. ICT which is viewed as support sources, should enable the users to remove all barriers to accessing and using web resources effectively to bring about an intellectually meaningful transformation. Learners need guidance and training in the selection and use of specific and reliable learning resources. Hence this study aims at understanding the views of the learners of English language towards the use of technology for learning purposes. Since there are only a few studies in India regarding this matter, this research becomes quite significant for setting future research trends in ICT and English Language Teaching (ELT).